Household Expenditure for Java in Health Costs Compared to The Island Java - Wira Iqbal; Mubassyir Hasan Basri; Limawan Budiwibowo (Faculty of Public Health, Andalas University, 2016)
The Health funding is a key element in the health system in various countries. This study aims to determine the cost of household expenditure on health in Indonesia. As well as to determine the effect of geografis location, economic status and ownership of insurance against household expenditure for health care costs in Indonesia. This research is analytic study with cross-sectional design that will explain the relationship of household expenditures for health care costs. The unit of analysis of this research is the data susenas in 2011. This study shows that the economic status, geographical location and insurance status affects the amount of health care costs households a month in Indonesia. In terms of the economic status of poor households that spending on health is considerably lower than richer households.There are significant differences between Java and outside Java, this is more evident on the rich. In terms of insurance status, type of insurance affect the amount of costs incurred, households with a health card insurance pay far less than households that have other types of insurance. This study found that household spending on health care costs in Java is higher than outside Java, and the persistence of household spending on health care costs in the poorest group in which the government has done with the guarantee program jamkesmas, Jamkesda and Jampersal.